ANALYSIS OF THE DISPUTE RESOLUTION MECHANISM OF THE TRIUMVIRATE MINISTER AS THE EXECUTOR OF PRESIDENTIAL DUTIES IN INDONESIA - Komang Yoga Saputra; I Nyoman Bagiastra (Transpublika Publisher, 2023)
The 1945 Constitution regulates the position of triumvirate ministers, including the Minister of Home Affairs, Minister of Foreign Affairs, and Minister of Defense, collectively empowered to replace the president and vice president in case of a vacancy. The exercise of this authority increases the likelihood of disputes among the three ministers while performing presidential duties in Indonesia. The conflicting implications of the triumvirate minister position and its assumed powers stem from the diverse backgrounds of the three different institutions. Therefore, a clear mechanism is necessary for resolving conflicts among triumvirate ministers. This study employs normative legal research methods with a statutory law approach, utilizing primary legal material and secondary legal materials such as books and journals. The findings reveal that the dispute resolution mechanism for triumvirate ministries is fundamentally within the purview of the Constitutional Court, as affirmed by the Constitution. However, a lack of detailed derivative regulations has led to a blur in norms related to the interpretation of state institutions outlined in the Constitution. This gap arises due to the absence of regulations that provide a comprehensive explanation of these state institutions.